2017
DOI: 10.18052/www.scipress.com/ilcpa.74.22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molarity on Structural and Optical Properties of Chemically Deposited Nanocrystalline PbS Thin Film

Abstract: Abstract. Thin films of PbS were deposited by chemical bath deposition (CBD) method under various molarities using lead acetate as Pb 2+ ion source, thiourea as S 2-ion source and ammonia as complexing agent at a fixed pH value of 9 under bath temperature of 333 K. Four different molarities of PbS thin films were prepared. The as-prepared films were characterized by using X-ray diffraction (XRD), X-ray fluorescence (XRF), EDX, field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…As shown in Table, observed d values for the sample are smaller than the standard d values. Similar result has been observed in the literature [27].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Table, observed d values for the sample are smaller than the standard d values. Similar result has been observed in the literature [27].…”
Section: Resultssupporting
confidence: 93%
“…In this analysis, eight reflections from the cubic PbS structure were considered. Results are presented in [27].…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that as deposition time increases optical band gap is reduced even though variation is not noticeable. The observed bandgap is in agreement with reported values [25,29].…”
Section: Optical Studiessupporting
confidence: 92%
“…This implies that lattice strain in PbS-2 film restricts the increase in particle size at the grain boundaries. Meanwhile the lower value of strain and high intensity in diffraction pattern for PbS-3 is indicative of the increased thickness with deposition time which comes in agreement with reported results [22,25].…”
Section: Structural Characterizationsupporting
confidence: 91%
“…As the solution concentration increases, more Cu and O atoms in the surface substrate are precipitated and they experience more interactions which contributes to an enlargement of the crystallites and leads to bigger grains and subsequently the enhancement of film's crystallinity [27]. Furthermore, the lattice defects along the grain boundaries are reduced due to the increase of crystallites size, which may lead to decreasing strain and dislocation densities [28], as seen in Table 1. The minimum values of δ and strain ԑ are found to be 3.1 × 10 10 line/cm 2 and 6.13 × 10 −4 respectively at solution molarity of 0.1 mol/L.…”
Section: Structural Propertiesmentioning
confidence: 99%